A Chickpea Revolution in Southern India - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2015)
This SPIA Impact Brief derives from the SPIA commissioned study Short Duration Chickpea Technology: Enabling Legumes Revolution in Andhra Pradesh, India (http://oar.icrisat.org/8831/).